Water quality analysis of old and new Phuleli Canal for irrigation purpose in the vicinity of Hyderabad, Pakistan. Issue 2 (27th January 2022) - Panhwar, Muhammad Yousif; Panhwar, Sallahuddin; Keerio, Hareef Ahmed; Khokhar, Nadar Hussain; Shah, Sabab Ali; Pathan, Nasreen
Abstract: Irrigation-water quality plays an important role in agriculture productivity. In this study, water quality of the old and new Phuleli canal located in Hyderabad, Pakistan, was characterized for irrigation purpose. Water samples were collected from four different locations of both the old and new Phuleli canal. Twelve different irrigation-water quality standards were assessed under the study: pH, Electricity Conductivity, Biochemical Oxygen Demand (BOD), Total Dissolved Solids, Chemical Oxygen Demand (COD), Dissolved Oxygen, Calcium, Magnesium, Sodium, Potassium, Sodium adsorption ratio, Fecal Coliforms. The results showed that the Electricity Conductivity ranges from 910–3, 090 MS/cm, Potassium 13–112 mg/l, BOD 61–285 mg/l, COD 97–361 mg/l and Fecal Coliforms 400–2, 350 MPN/100 ml concentrations in water of both canals were higher than the National Environmental Quality Standards permissible limits. It was found that the water quality parameters were higher than the permissible pollution level of canal water for the use of irrigation in agriculture. HIGHLIGHTS: Water quality of the old and new Phuleli canal located in Hyderabad Pakistan was characterized for irrigation purpose. Twelve different Irrigation-water quality standards were assessed under the study. Twelve species were focused under the study. Irrigation water was highly contaminated, when it passed through the urban area. Due to high contamination, indirect method can be used for agriculture purposes. Graphical Abstract